2003
DOI: 10.1002/polb.10584
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of hydrophilic poly(propylene imine) dendrimers in aqueous solutions by 1H NMR relaxation

Abstract: The local dynamics of three poly(propylene imine) dendrimers with hydrophilic triethylenoxy methyl ether terminal groups were studied in D2O by the measurement of the 1H NMR relaxation times, which were treated with the Lipari–Szabo model‐free approach. The results showed that the overall mobility increased with temperature and decreased with increasing dendrimer size. An Arrhenius trend was observed for both overall and local motions. The activation energy of overall tumbling increased from 11.3 to 17.5 kJ/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…Phys. 130, 044907 ͑2009͒ 44 clearly show that for different dendrimers ͑n =2, 4, 5͒ the positions of the 1 / T 1H maxima for all dendrimer segments coincide.…”
Section: -7mentioning
confidence: 82%
“…Phys. 130, 044907 ͑2009͒ 44 clearly show that for different dendrimers ͑n =2, 4, 5͒ the positions of the 1 / T 1H maxima for all dendrimer segments coincide.…”
Section: -7mentioning
confidence: 82%
“…A computational study carried out by Lescanec and Muthukumar [23] 12 years later contradicted the DGH prediction by finding that many terminal ends of a dendrimer do not remain at the dendrimer periphery but rather fold back into the dendrimer interior. Since then, numerous theoretical [12,13, and experimental [4,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] studies have been conducted which led to the current consensus [55] that the end groups of dendrimers made of a flexible backbone are distributed throughout the dendrimer interior in a core-dense manner. Only in a few rare studies were the terminal groups found to lay at the dendrimer periphery, when the ends were subject to some repulsive electrostatic forces [35,56,57] or attractive hydrogen-bond interactions [58] or the dendrimer was made of stiff repeating units [50].…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical standpoint however, the continuous increase in dendrimer density with generation number leads to the prediction that a crossover generation exists where the available free volume inside the dendrimer vanishes. Considering the importance of the end groups for applications, this decrease in free volume with increasing G led numerous theoreticians and experimentalists [4,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] to question what became of the end groups in higher generation dendrimers as they might be trapped in the congested dendrimer interior. The first theory dealing with this issue was proposed by de Gennes and Hervet (DGH) [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the above mentioned applications are not only determined by the dendrimer structure but also by their dynamical properties, much less attention has been drawn to the flexibility, i.e., internal dynamics of dendrimers. Experimental studies on the internal dynamics in solutions include predominantly NMR investigations [29][30][31][32][33][34] and some experiments using neutron spin-echo ͑NSE͒ spectroscopy. 8,9 The latter are summarized in more detail below.…”
Section: Introductionmentioning
confidence: 99%